Nation, Law and Justice. The Debate about the New International Order in Italian Society, 1840-1848 - Šedivý, Miroslav (My University, 2022)
In the 1840s Italian society expressed a deep mistrust of the international order that had been created in Europe after the Napoleonic Wars. This came as a result of the assertive and often illegal politics followed by the Great Powers: a considerable number of Italians believed so that the world was dominated by the strength of material power instead of the written law. With this conviction, the idea of political unity or even the unification of Italian territories was gradually obtaining supporters within the quickly spreading nationalist movement. At the same time, the desire to change the post-Napoleonic order not only in Italy but also in the whole of Europe, by replacing it with a new one based on the principle of nationhood ensuring greater justice and a more stable peace among free European nations, became a significant topic of nationalist discourse. The aim of the paper is to shed a new light on this important phenomenon existed since the mid 19th century not only in Italian nationalism, even if still neglected by historical and legal scholarship. Moreover, the essay wants to explain the reasons behind both its origins and failure, highlining how the latter caused negative consequences for future relations among European countries and nations.
Národ, právo a spravedlnost: Debata o novém mezinárodním pořádku v italské společnosti 1840-1848
Keywords: Nation; Law; Justice; Italy; Europe; Post-Napoleonic Order; národ; právo; spravedlnost; Itálie; Evropa; postnapoleonský pořádek